2018
DOI: 10.1101/249573
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quantitative Trait Loci ControllingPhytophthora cactorumResistance in the Cultivated Octoploid Strawberry (Fragariaxananassa)

Abstract: The cultivated strawberry, Fragaria x ananassa (Fragaria spp.) is the most economically important global soft fruit. Phytophthora cactorum, a water-borne oomycete causes economic losses in strawberry production globally. A bi-parental cross of octoploid cultivated strawberry segregating for resistance to P. cactorum, the causative agent of crown rot disease, was screened using artificial inoculation. Multiple resistance quantitative trait loci (QTL) were identified and mapped. Three major effect QTL (FaRPc6C, … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 46 publications
(66 reference statements)
0
7
0
Order By: Relevance
“…cactorum is a persistent pathogen of strawberry and an economically significant pathogen of apple [ 41 ]. Genomic resources are available for these hosts [ 84 87 ], and recent work has identified resistance-associated QTL for cultivated strawberry [ 19 ]. Despite this, genomic resources for the pathogen are limited to identification of ESTs expressed during infection [ 88 ] and transcript expression during oospore germination characterized [ 49 , 89 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…cactorum is a persistent pathogen of strawberry and an economically significant pathogen of apple [ 41 ]. Genomic resources are available for these hosts [ 84 87 ], and recent work has identified resistance-associated QTL for cultivated strawberry [ 19 ]. Despite this, genomic resources for the pathogen are limited to identification of ESTs expressed during infection [ 88 ] and transcript expression during oospore germination characterized [ 49 , 89 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to these Phytophthora pathosystems, strawberry resistance to P . cactorum appears to be quantitative [ 19 22 ], and no race structure has been reported to date. As such, resistance is not determined by a single gene-for-gene recognition, as often associated with RxLR effectors [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…P. cactorum is a persistent pathogen of strawberry and an economically significant pathogen of apple (Erwin and Ribeiro 1996). Genomic resources are available for these hosts (Antanaviciute et al 2012; Hirakawa et al 2014; Davik et al 2015; Daccord et al 2017), and recent work has identified resistance-associated QTL for cultivated strawberry (Nellist et al 2018). Despite this, genomic resources for the pathogen are limited to identification of ESTs expressed during infection (Chen et al 2011) and transcript expression during oospore germination characterized (Chen et al 2014; Chen et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative resistance to Phytophthora diseases has also been associated with basal defence (Vega-Sánchez et al 2005; Thomas et al 2007). Accordingly, this study characterises a broad range of effector genes and provides candidates to investigate the basis of quantitative strawberry resistance to P. cactorum (Denoyes-Rothan et al 2004; Shaw et al 2006; Shaw et al 2008; Nellist et al 2018). RxLR effectors are still priority candidates disease related pathogen genes for functional study of strawberry resistance to P. cactorum , particularly homologs of AvrSmira2 characterised avirulence genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation